Homelessness and mental illness : exploring the lived experience in India - Bhattacharya, Prama (Routledge, 2024)
"This book explores the trajectories of social suffering, exclusion, and victimization of homeless persons with mental illness in India. It uses a Critical Ethnographic approach to study their lived experiences associated with downward mobilization and the challenges in the process of recovery and empowerment. Using theoretical and methodological implications, the volume highlights the experiences of this marginalized population through their voices instead of relying on epidemiological data only. It presents stories that show how such persons celebrate their abilities to tolerate all forms of ostracization and endure the sufferings with fortitude. The book discusses how 'hope', as a part of their experience, catalyzes the process of recovery and empowerment and helps them develop meaningful social ties to access valued social resources. It further brings to light the difficulties experienced by service providers in providing service due to a lack of resources and support at a systemic level and awareness about mental illness among various stakeholders. This book will be of interest to students, teachers, and researchers of social psychology, clinical psychology, community psychology and sociology. It will also be helpful for academicians, policymakers, social workers, mental health practitioners, and NGO personnel"-- Provided by publisher.
Keywords: Mentally ill homeless persons -- India.; Mentally ill homeless persons -- Mental health services -- India.; Homeless persons -- Mental health -- India.; Homeless persons -- Mental health services -- India.; Mentally ill -- India.; Social psychiatry -- India.; elektronické knihy; electronic books